2020
DOI: 10.1002/14651858.cd012559.pub2
|View full text |Cite
|
Sign up to set email alerts
|

Hormone replacement therapy after surgery for epithelial ovarian cancer

Abstract: Hormone replacement therapy a er surgery for epithelial ovarian cancer (Review)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
23
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 53 publications
0
23
0
2
Order By: Relevance
“…The authors, however, acknowledged that there were methodological limitations in the included studies and recommended the need for well-designed and large-scale RCTs to further assess this. Saeaib et al (2020) reported a Cochrane review (three RCTs, involving 350 women) on HRT after surgery for epithelial ovarian cancer. The review concluded that HRT may slightly improve overall survival in women who have undergone surgical treatment for epithelial ovarian cancer, but the quality of the evidence was low (HR 0.71; 95% CI 0.54-0.93).…”
Section: Hrt After Cancermentioning
confidence: 99%
“…The authors, however, acknowledged that there were methodological limitations in the included studies and recommended the need for well-designed and large-scale RCTs to further assess this. Saeaib et al (2020) reported a Cochrane review (three RCTs, involving 350 women) on HRT after surgery for epithelial ovarian cancer. The review concluded that HRT may slightly improve overall survival in women who have undergone surgical treatment for epithelial ovarian cancer, but the quality of the evidence was low (HR 0.71; 95% CI 0.54-0.93).…”
Section: Hrt After Cancermentioning
confidence: 99%
“…A recent systematic review article from the Cochrane Database comes to the conclusion that HRT slightly improves the overall survival of women who have undergone surgical treatment because of epithelial ovarian cancer but the evidence certainty for this is low. The authors emphasise that the results can be interpreted with caution and that future well-designed RCTs are required to examine the oncological safety 19 .…”
Section: Hrt After Ovarian Cancermentioning
confidence: 99%
“…Eine neue systematische Übersichtsarbeit von Cochrane Database kommt zu der Schlussfolgerung, dass eine HRT das Gesamtüberleben bei Frauen, die sich einer chirurgischen Behandlung wegen epithelialer Ovarialkarzinome unterzogen haben, geringfügig verbessert, aber die Evidenzsicherheit hierfür ist gering. Die Authoren betonen, dass die Ergebnisse mit Vorsicht interpretiert werden können, und dass zukünftige gut konzipierte RCTs erforderlich sind, um die onkologische Sicherheit zu prüfen 19 .…”
Section: Hrt Nach Ovarialkarzinomunclassified
“…Summary of evidence and recommendations for practice with the use of MHT in EOC survivors and some have even suggested improved outcomes with MHT. A 2020 Cochrane review15 on this topic included the three randomised trials for comparison.They showed that the studies were heterogenous for the type of MHT used, stage of EOC and age of the patients and at high risk of several biases. Ultimately, they concluded that the certainty of evidence was low for improvements in OS (hazards ratio (HR) 0.71; 95% CI 0.54-0.93), the RCTs were powered for a PFS benefit only and no difference was seen in PFS (HR 0.76; 95% CI 0.57-1.01; P = NS).…”
mentioning
confidence: 99%
“…Menopause and Andropause Society and IGCS suggesting no contraindication to use,15,16 while others advise exercising caution given the absence of RCTs specific to cervical adenocarcinomas.For vaginal and vulval SCC, oophorectomy is rarely required; however, MHT may still be required following radiotherapy-induced ovarian failure. It is generally considered safe to use MHT in these groups given the lack of oestrogen receptors.…”
mentioning
confidence: 99%